Critical Analysis on Historiography of Gamelan Bebonangan In Bali - Santosa, Hendra (Paramita: Historical Studies Journal, 2020)
Historical sources on gamelan Bebonangan refer to the different shapes and forms of the ensemble. This inevitably results in perplexity on the origin, shapes, and forms of gamelan Bebenongan. The paper, therefore, aims to redress the confusion by rewriting it through critical history, a type of criticism on historical sources related to the term gamelan Bebonangan in Bali. The method used for the paper is historical approaches that include heuristics, criticism, interpretation, and historiography as the finale. The word bebonangan is not found in historical sources of Balinese karawitan in the form of Old Javanese literature, which is today preserved in Bali and the Balinese literature itself. The only literary work that mentions these pencon-ed instruments is the Book of Pararaton, calling the as reyong instruments. The Book of Prakempa refers to the instruments in names such as reyong barangan and reyong pangageng. By indicating that the reyong instrument becomes the main instrument, one may expect peculiarity in the claims. It may be pointed out that opinions have been led in the beginning by the foreign influence to impose the view to the Balinese to challenge their own identity and, at the same time to be applauded for their arts and culture.Sumber sejarah tentang gamelan Bebonangan yang menunjuk bentuk dan wujud yang berbeda. Hal ini tentu saja menyebabkan kesimpang siuran tentang asal-usul dan wujud gamelan Bebonangan itu sendiri. Oleh karenanya penulisan ini bertujuan untuk meluruskan kesimpangsiuran yang terjadi dengan menuliskannya melalui kritik terhadap sumber-sumber sejarah istilah gamelan Bebonangan di Bali. Metode yang dipergunakan yaitu metode sejarah yaitu heuristik, kritik, interpretasi atau penafsiran, dan terakhir adalah historiografi. Kata bebonangan tidak ditemukan dalam sumber-sumber sejarah karawitan Bali yang berupa literatur kesusastraan Jawa Kuna yang sekarang diawetkan di Bali dan literatur kesusastraan Bali sendiri. Satu-satunya karya kesusastraan yang menyebutkan instrumen berpencon ini adalah kitab pararaton yang menyebutnya dengan instrumen reyong. Prakempa menyebutkan instrumen-instrumen gamelan Bebonangan antara lain reyong Barangan dan reyong Pangageng. Merujuk hal tersebut dimana instrumen reyong merupakan instrumen utama, maka tentulah hal ini menjadi sebuah keanehan. Sepertinya telah terjadi penggiringan sejak awal, adanya pengacauan asing telah memaksakan orang Bali untuk mempertanyakan dasar identitas mereka, pada saat yang sama mereka juga mendapat sanjungan untuk seni dan budayaannya.